Code Mixing: Why Do English Teachers Use It in the Classroom - Puan Dianty; Hendra Heriansyah (Research in English and Education Journal, 2021)
The purpose of this study was to investigate the reasons of the English teachers use code mixing in teaching English at SMP Negeri 6 Banda Aceh. Three English teachers were purposively selected as the participants in this study. Qualitative research was employed as the research method to collect the data through an interview. The findings of this study showed that the teachers of English used code mixing in the language classroom was to clarify the speech content for interlocutors (students), which was intended to give a clearer understanding when explaining learning materials so that students did not get confused about the teacher’s explanations. In addition, repeating for clarification was another reason of English teachers use code mixing in the classroom. It was conducted to clarify if the teacher’s instructions were not understandable by students. For this purpose, she inserted some words or phrases in Indonesian so that the student got the meaning and understood what the teacher said. In conclusion, the use of code mixing has significantly brought positive impacts on EFL learning classroom to help students in understanding learning materials and the teacher‟s explanations.